Identification of Potential High-Risk Patients on the Basis of PROMs in a Certified Centre for Joint Replacement (EndoProthetikZentrum) Using the Example of Hip Arthroplasty - Osmanski-Zenk, Katrin; Klinder, Annett; Ellenrieder, Martin; Darowski, Martin; Goosmann, Martin; Mittelmeier, Wolfram (The Journal of Hip Surgery, 2024)
Background In addition to clinical parameters, the subjective assessment by the patient to evaluate the operative outcome of an arthroplasty is becoming increasingly important. Questionnaires are used to identify patients who have not achieved the treatment goal at an early stage so that further interventions can be indicated.Material and Methods A questionnaire consisting of different PROMs was completed pre- and 3 months postoperatively by patients who had been treated with a hip arthroplasty. A standardised follow-up examination of these patients was carried out 12 to 16 weeks postoperatively, after which it was determined whether further therapy was necessary to achieve the treatment goal. Different consequences were defined for this.Results Significant differences were found between the groups of consequences of follow-up examinations over both time points, but also when postoperative scores were considered exclusively. Furthermore, the correlations for the postoperative scores and some consequences of the clinical follow-up for the Oxford Hip Score (OHS), the OHS functional score and the Euroquol-5D show moderate effects. Thus, the collection of these postoperative scores is sufficient to identify potential high risk patients. Based on a receiver operating characteristic (ROC) analysis, threshold values could be determined for these scores, for which a follow-up examination is recommended.Conclusion Patients who could not achieve functional improvement, pain reduction and improvement in quality of life after implantation of a total hip replacement must be identified at an early stage. The results of our study show that with the help of the Oxford Hip Score and Euroquol-5D, which are answered by the patients three months postoperatively, such high risk patients can be identified. This finding is an added value for the further development of the EndoCert certification system and holistic quality assurance in arthroplasties, while the personnel and time effort remain manageable.
Keywords: EndoCert; follow-up study; hip arthroplasty; Oxford Score; Euroquol-5D